Characterization of Biochar Obtained from Olive and Hazelnut Prunings and Comparison with the Standards of European Biochar Certificate (E.B.C.). (10th June 2016) - Abenavoli, Lorenzo M.; Longo, Leonardo; Proto, Andrea R.; Gallucci, Francesco; Ghignoli, Alessio; Zimbalatti, Giuseppe; Russo, Diego; Colantoni, Andrea
Abstract: Concerns about climate change and food productivity have spurred interest in biochar, a form of charred organic material, typically applied in agriculture to improve soil productivity and as mean of carbon sequestration. An innovative approach in agriculture is the use of agro-industrial waste for the production of soil fertilizers for agricultural purposes and as a source of energy. A common agricultural practice is to burn crop residues in the field to produce ashes that can be used as soil fertilizers. This approach is able to supply plants with certain nutrients such as Ca, Na, K, Mg, B, S and Mo. However the lack of N and P in the ashes, together with the occasional presence of heavy metals (Ni, Pb, Cd, Se, Al, etc.), has a negative effect on soil and therefore crop productivity. This work describes the opportunity to create an innovative supply chain from agricultural waste biomass. Olive ( Olea europaea L.) and hazelnut ( Corylus avellana L.) pruning residues represent a major component of biomass waste in the area of Viterbo (Italy). In this study, we evaluated the production of biochar from these residues. Furthermore, a physico-chemical characterization of the produced biochar was performed to assess the quality of the two biochars according to the standards of the European Biochar Certificate (EBC). The results of this study indicate the cost-effective production of high- quality biochars from olive and hazelnuts biomass residues.